2006
DOI: 10.1242/jeb.02313
|View full text |Cite
|
Sign up to set email alerts
|

Having the nerve to home: trigeminal magnetoreceptor versusolfactory mediation of homing in pigeons

Abstract: SUMMARY The ability of pigeons to find their way home from unfamiliar sites located up to hundreds of kilometers away is well known, but the mechanisms underlying this ability remain controversial. One proposed mechanism is based on the suggestion that pigeons are equipped with magnetoreceptors that can enable the detection of either the earth's magnetic field and/or magnetic field anomalies in the local terrain over which the pigeons fly. Recent reports have suggested that these magnetoreceptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
1
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(68 citation statements)
references
References 26 publications
3
62
1
2
Order By: Relevance
“…However, the results reported by Wiltschko et al actually speak against crucial involvement of the trigeminal system in navigation, as the anaesthetised pigeons showed unimpaired navigational abilities. This is consistent with what was reported in a series of experiments in which the V1 of homing pigeons were lesioned before release at unfamiliar sites (Gagliardo et al, 2006;Gagliardo et al, 2008;Gagliardo et al, 2009). In no case did lesioning V1 result in impairment in homing performance, and strikingly, birds with an intact V1 were unable to home if the olfactory nerve was severed.…”
Section: Introductionsupporting
confidence: 90%
“…However, the results reported by Wiltschko et al actually speak against crucial involvement of the trigeminal system in navigation, as the anaesthetised pigeons showed unimpaired navigational abilities. This is consistent with what was reported in a series of experiments in which the V1 of homing pigeons were lesioned before release at unfamiliar sites (Gagliardo et al, 2006;Gagliardo et al, 2008;Gagliardo et al, 2009). In no case did lesioning V1 result in impairment in homing performance, and strikingly, birds with an intact V1 were unable to home if the olfactory nerve was severed.…”
Section: Introductionsupporting
confidence: 90%
“…Such procedures impair navigation even when visual cues are available (59). Although homing pigeons also orient by using geomagnetic fields (60), this input appears to be weighted less heavily than olfaction in experimentally displaced homing pigeons (61) and in migrating songbirds (62). Such experimental evidence for the primacy of olfactory inputs in navigation, across multiple diurnal bird orders, lends strong credence to the OS hypothesis.…”
Section: Birdsmentioning
confidence: 79%
“…Mora et al (14) showed in a conditioning experiment that pigeons required intact ophthalmic branches of the trigeminal nerve (V1) to detect a strong magnetic anomaly, although Gagliardo et al (35)(36)(37) showed that V1 sectioned pigeons of all ages and levels of homing experience homed as well as control birds. Together, these results suggest that, although pigeons can detect magnetic information, V1 is not generally required for successful homing in this species.…”
Section: Discussionmentioning
confidence: 99%